Enhancing English Learning: Self-Determination in Indonesia Digital Classrooms - De Vega, Nofvia; Rahayu (Institut Agama Islam Negeri Parepare, 2023)
This study explored the experiences of students with technology-integrated English language instruction at two Indonesian universities, Universitas Borneo Tarakan (UBT) and Universitas Sawerigading Makassar (UNSA). The primary aim was to understand the influence of perceived autonomy, competence, relatedness, and motivation levels on English language learning outcomes. Utilizing a mixed-methods approach that combined survey data and thematic analysis of interviews, we found that students generally reported high levels of these factors. Minor differences were observed between UBT and UNSA in terms of perceived autonomy and competence-relatedness. Positive correlations were identified between these factors and improved performance in English language learning; for example, autonomy positively correlated with English learning outcomes (r = 0.60*), as did competence (r = 0.65*), relatedness (r = 0.62*), and motivation levels (r = 0.70*). These findings highlight the importance of fostering learners' sense of autonomy, competence building, and relatedness in technology-enhanced instruction settings to promote intrinsic motivation according to Self-Determination Theory (SDT). Further research is recommended to explore other potential influencing factors such as individual attitudes towards technology or external factors like teaching quality or course design.